Case Report: Successful avoidance of etoposide for primary hemophagocytic lymphohistiocytosis-induced multiple organ dysfunction syndrome using emapalumab - Hahn, Timothy J.; McKeone, Daniel J.; Beal, James W.; Ericson, Jessica E.; Halstead, E. Scott (Frontiers in Pediatrics, 2024)
We describe the case of an infant who presented with simple rhinovirus/enterovirus bronchiolitis whose condition worsened with rapid progression to multiple organ dysfunction syndrome (MODS). The patient was presumed to have either primary or secondary hemophagocytic lymphohistiocytosis (HLH) and immune modulation with dexamethasone, anakinra and intravenous immunoglobulin was initiated. Given the organ dysfunction, etoposide was avoided in favor of the interferon gamma antagonist, emapalumab, at a dose of 6 mg/kg. The patient's organ failure improved and inflammatory markers decreased. Flow cytometry revealed an absence of perforin expression by cytotoxic cells, and subsequent genetic analysis confirmed homozygous pathogenic mutations in the perforin gene. This case highlights that etoposide can be avoided in cases of primary HLH, the possible benefit of an elevated starting dose of emapalumab, and the contribution offered by a multi-specialty team approach to complex diagnosis.